Correlation between fucoxanthin contents in Turbinaria sp.and sea water nutrients at Binuangeun and Krakal Coasts - Januar, Hedi Indra; Wikanta, Thamrin (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2011)
Fucoxanthin pigment is a potential compound in nutraceutical. It is commonly found in algaesuch as in Turbinaria sp.,a very abundant species in Indonesian coastal. To maximize theproduction of fucoxanthin for the development of nutraceutical industry in the coastal area, it isimportant to identify the optimal environmental parameters for its biosynthesis. It has been reportedthat nitrogen and or phosphate nutrients affect the growth of algae. Therefore, this paper aimed toobtain an optimal environment for Turbinaria sp. to produce fucoxanthin based on correlationanalysis. Correlated data were fucoxanthin isolated from Turbinaria sp.that was collected fromKrakal (Yogyakarta) and Binuangeun (Banten) coasts. Fucoxanthin contents in each sample werecompared based on the peak areas in chromatogram after 1 mg injection of n-hexane extract ofT. decurrrens in the HPLC system. The analysis results showed that the peak areas of fucoxanthinwere significantly different among sampling locations (P = 7.99 x 10-6), sampling periods (P = 6 x10-3) and interaction of both (P = 3 x 10-3). Whereas the correlation analysis revealed that interactionbetween phosphate and temperature could be a predictor that strongly (R = 0.986) and significantlycorrelated (P = 1.09 x 10-7) with the peak areas of fucoxanthin (R2= 96.5%). These results were inline with growth limiting factor in seawater and the function of fucoxanthin as ultraviolet protector.Based on these results, it is suggested that the suitable location for fucoxanthin production is in thearea of agricultural run-off that contains an elevated concentration of dissolved phosphate.